Perhitungan dan Upaya Peningkatan Output Rate di PT. X - Gary Limanto Soegiarto; Liem Yenny Bendatu (Jurnal Titra, 2015)
PT. X hasn’t yet measured output rate in production process, so company would like to measure the actual output rate. The measurement and effort to increase the output rate is performed for Merbau, Bangkirai, and Torem wood species on Line Preparation that consists of Planer, Crosscut, and Ripsaw process. Actual output rate in Planer for each wood species are respectively 0,0676, 0,0510, dan 0,0565 m3/menit. Actual output rate in Crosscut for each wood species are respectively 0,0260, 0,0298, dan 0,0257 m3/menit. Actual output rate in Ripsaw for each wood species are respectively 0,0305, 0,0315, dan 0,0318 m3/menit. This actual output rate is not optimal yet, could be seen from the Availability Ratio on Line Preparation that’s below World Class Company’s Availability Ratio (90 %). Availability Ratio in Planer for each wood species are respectively 72.60%, 81.91%, and 82.96%. Availability Ratio in Crosscut for each wood species are respectively 62.89%, 67.93%, and 64.08%. Availability Ratio in Ripsaw for each wood species are respectively 73.99%, 74.34%, and 74.33%. The effort to increase the output rate is then compiled such as design of additional tools for production machines, Work Instruction arrangement, and layout change in Line Preparation.